Parental guidance and the development of children's moral reasoning in social media use: Patterns and implications - Utomo, Prio; Annisa, Dona Fitri; Isa, Nor Junainah Mohd; Iloakasia, Adaobi Jennifer (Jurnal Anifa: Studi Gender dan Anak, 2025)
The rapid advancement of technology and the widespread use of social media have introduced new challenges for parents in guiding their children's moral development. This study explores the patterns of parental guidance in shaping children's morality within the context of social media use and examines its impact on their moral growth. Employing a qualitative approach with a phenomenological method, the research was conducted with parents residing in Citeureup Village, North Cimahi District. Data were collected through in-depth interviews, participatory observation, and documentation, and then analyzed using data reduction, validation, and conclusion-drawing techniques. The findings reveal three primary patterns of parental guidance: preventive, persuasive, and collaborative. These strategies are actively utilized by parents to nurture their children's moral awareness in the digital age. The study concludes that parental presence and active engagement play a crucial role in children's moral development—particularly in shaping ethical behavior, social interaction, and a sense of responsibility—ultimately fostering more thoughtful and responsible digital citizens. This research offers valuable insights for parents, educators, and policymakers in developing effective strategies to support moral and character education in the digital era.